The analysis of complex thermal bridges solutions in terms of improving their thermal parameters - Kulczewska, Sylwia; Jezierski, Walery (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
The article presents the analysis of complex thermal bridges solutions which occur in the fixing nodes of ventilated facade and the way of taking into consideration them in thermal calculations. On the basis of this analysis, a number of factors which may affect the thermal parameters of thermal bridges were detected. However they are not reflected in the formulas specified in current standards. Therefore, new approaches and correlations, that will precisely determine the physico-technical parameters of similar fixing nodes, should be looked for.